2022
DOI: 10.1016/j.ijsu.2022.106856
|View full text |Cite
|
Sign up to set email alerts
|

Automated surgical workflow identification by artificial intelligence in laparoscopic hepatectomy: Experimental research

Abstract: Background: To perform accurate laparoscopic hepatectomy (LH) without injury, novel intraoperative systems of computer-assisted surgery (CAS) for LH are expected. Automated surgical workflow identification is a key component for developing CAS systems. This study aimed to develop a deep-learning model for automated surgical step identification in LH. Materials and methods: We constructed a dataset comprising 40 cases of pure LH videos; 30 and 10 cases were used for the training and testing datasets, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Laparoscopic cholecystectomy is the most commonly used procedure to test automated surgical workflow recognition models 4 . Other procedures that have been used for this task include liver surgery 27 , gynecologic surgery 28 , colorectal surgery 29 , bariatric surgery 30 , and urological surgery 31 . In our study, owing to the standardized process of RLLS, multilevel surgical workflow recognition achieved relatively high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy is the most commonly used procedure to test automated surgical workflow recognition models 4 . Other procedures that have been used for this task include liver surgery 27 , gynecologic surgery 28 , colorectal surgery 29 , bariatric surgery 30 , and urological surgery 31 . In our study, owing to the standardized process of RLLS, multilevel surgical workflow recognition achieved relatively high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported a model for transanal endoscopic total mesorectal excision with an accuracy rate of 93.2% [ 24 ]. Sasaki et al [ 25 ] reported a phase recognition model for laparoscopic liver resection with an accuracy rate of 94.7%. Takeuchi et al [ 26 ] reported about robotic esophagectomy with an accuracy rate of 84%.…”
Section: Surgery Phase Recognitionmentioning
confidence: 99%